1986
DOI: 10.1002/clc.4960091107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of furosemide and slow‐release furosemide on thoracic fluid volumes

Abstract: Summary:Transthoracic electrical impedance (TEI) was used to assess the relative effectiveness of a 60 mg sustained-release furosemide preparation (FR) and a 40 mg standard furosemide tablet (F), in reducing the fluid content in the thoracic cavity. A double-blind crossover study was performed, in which 12 men with a history of one or more myocardial infarctions and mild left heart failure treated with 40 mg furosemide once daily participated. The trial, lasting 28 days, was divided into two 14-day periods. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…More recent studies found that the aorta contributed to only about 1% of the total impedance measurement, the skeletal muscle represented the highest contribution (>50%), and the measure was highly sensitive to changes in impedance in the upper thorax [ 33 , 34 ]. Despite the limitations and the additional components that were captured by the TBI, it had clinical importance, as the intra-patient directional changes in the impedance were indicative of directional changes in the thoracic fluid [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…More recent studies found that the aorta contributed to only about 1% of the total impedance measurement, the skeletal muscle represented the highest contribution (>50%), and the measure was highly sensitive to changes in impedance in the upper thorax [ 33 , 34 ]. Despite the limitations and the additional components that were captured by the TBI, it had clinical importance, as the intra-patient directional changes in the impedance were indicative of directional changes in the thoracic fluid [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…There is some evidence that, apart from using the variable impedance signal to measure cardiac output, the baseline signal can be used to measure the thoracic fluid content, a measure of a patient's total volume state 85 . This signal has been used to follow changes in thoracic fluid content during diuretic therapy 86,87 and for titrating fluid shifts during haemodialysis 88 . However, the presence of too much fluid in the chest can cause so low a baseline impedance signal ( Z 0 < 15 Ω) that it interferes with accuracy 43,89 .…”
Section: Resultsmentioning
confidence: 99%
“…Although one study suggested that knowledge of ICG parameters can alter a physician's treatment plans (24), and others have suggested that ICG parameters improve when patients receive effective drugs for heart failure (25,26), it is not clear whether ICG-directed modifications improve clinical outcomes beyond that expected if physicians responded appropriately to clinical signals in the absence of ICG data. In the Evaluation Study of Congestive Heart Failure and Pulmonary Artery Catheterization Effectiveness (ESCAPE) (27), the use of in-hospital invasive hemodynamic measurements to titrate treatment failed to alter long-term outcomes, but such assessments were not repeated during the period of follow-up.…”
Section: Discussionmentioning
confidence: 98%